Analisis Usability Website Simapres Pemerintah Kabupaten Wonogiri dengan Pendekatan System Usability Scale - Putra, Perdana Suteja; Brilianti, Grahita Prisca; Anugerah, Adhe Rizky (Jurnal Teknik, 2025)
This study aims to evaluate the usability of the Simapres website of the Wonogiri Regency, which is used to manage scholarships for students from state universities in Wonogiri. Usability was assessed using the System Usability Scale (SUS) method, which includes ten statements to measure effectiveness, efficiency, and user satisfaction. The study involved 15 respondents who were scholarship recipients in Wonogiri. The results show that the Simapres website received an average SUS score of 80.3, which falls into the "Acceptable" and "Excellent" categories based on user ratings. Although the website was rated as effective and efficient, some respondents provided suggestions for improvements in features and user interface. This study provides recommendations for system improvements to enhance user experience and the quality of technology-based public services in Wonogiri.